2014
DOI: 10.1089/pho.2014.3732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Surface Treatments on the Bond Strength of Acrylic Denture Teeth to Polymethylmethacrylate Denture Base Material

Abstract: Lasing of the ridge lap area to enhance the bond strength of acrylic resin denture teeth to PMMA denture base resin might be an alternative to wetting with MMA monomer. To overcome tooth debonding, surface treatment of the ridge lap area should be performed as part of denture fabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 28 publications
1
29
0
2
Order By: Relevance
“…More recently, it was found that shear bond strength was significantly improved when surface treatments were carried out by laser compared to mechanical and/or chemical surface treatments. 37 This option could also be explored in future to further improve the bond strength of zirconia-PMMA nanocomposites. Considering the current limitation of the test procedure following the British Standard other testing methods such as micro shear tests could also be explored to obtain more accurate results.…”
Section: Dovepressmentioning
confidence: 99%
“…More recently, it was found that shear bond strength was significantly improved when surface treatments were carried out by laser compared to mechanical and/or chemical surface treatments. 37 This option could also be explored in future to further improve the bond strength of zirconia-PMMA nanocomposites. Considering the current limitation of the test procedure following the British Standard other testing methods such as micro shear tests could also be explored to obtain more accurate results.…”
Section: Dovepressmentioning
confidence: 99%
“…It is soluble in organic solvents, slightly soluble in water, and is prone to addition polymerization. MMA and PMMA are common biomedical materials for fast dental prosthesis in stomatology, with very stable chemical properties [16, 17]. The polymerization process of MMA and PMMA can be divided into the following six phases: (1) wet sand period: MMA has not yet penetrated into PMMA but exists among the PMMA particles.…”
Section: Discussionmentioning
confidence: 99%
“…Grando, Pacheco, Botega, Hirakata, and Hilgert[ 15 ] reorted no significant difference in the wear resistance of different brands' (Trilux, Soluut PX) teeth. Akin, Kirmani, Tugut, and Coskum (2014)[ 16 ] worked upon the effects of different surface treatments in the ridge lap area of acrylic resin teeth on shear bond strength to heat polymerized poly (methyl methacrylate) (PMMA) denture base resin. They concluded to vanquish tooth debonding, surface treatment should be included as a part of denture fabrication.…”
Section: Discussionmentioning
confidence: 99%